+0  
 
+5
64
1
avatar

From the quadratic equations from the following:

 

 

Problem 1:

 

If 

f(2)=f(4)=0, f(3)=−2.

 

 

Problem 2:

 

If

 

Zeroes at 1± sqrt(2),  y-intercept at –4.

Guest Feb 26, 2017
Sort: 

1+0 Answers

 #1
avatar+77035 
0

Problem 1:

If 

f(2)=f(4)=0, f(3)=−2

 

x = 2  and x = 4 are roots    and the vertex  lies at  (3, -2)......so we know that

 

0  = a(2 - 3)^2  - 2   simplify

 

0 = a (-1)^2  - 2

 

0 =  a - 2   →   a = 2

 

So...our function is f(x)  = 2(x - 3)^2 - 2

 

Check   that x = 4 produces a zero

 

2(4 - 3)^2 - 2    =   2(1)^2  - 2   =   2 - 2  = 0

 

 

Problem 2:

If

Zeroes at 1± sqrt(2),  y-intercept at –4

 

The  x value of the vertex will be the average of the sum of the roots =

  [  1 + sqrt (2) +  1 - sqrt(2) ] / 2    = 2 / 2   = 1

And the x coordinate of the vertex  =  -B/ [ 2A]   implies that

-B/ [2A]  = 1   which implies that

-B  =  2A   which implies that

B = -2A

 

So  we have the following :

 

y  =  Ax^2  + Bx + C     and substituting for B

 

y = Ax^2  - (2A)x + C

 

And since the y intercept is at - 4 , then

 

-4  = A(0)^  -2A(0)  + C

 

-4  =  0 + 0 + C

 

-4 = C

 

So we have that

 

y = Ax^2 -2Ax - 4

 

And we know that

 

0  =  A(1 + sqrt(2))^2  - 2A(1 + sqrt(2))   - 4

 

4 = A ( 1 + 2sqrt(2) + 2)  - 2A  - 2Asqrt(2)

 

4 =  A + 2Asqrt(2) + 2A - 2A - 2Asqrt(2)

 

4 = A       ....    and  B  = -2A =  -8

 

So  we have

 

y = 4x^2 - 8x - 4

 

Here's a graph that confirms this : https://www.desmos.com/calculator/ba8scvgskt

 

 

cool cool cool

CPhill  Feb 26, 2017

7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details